Two-dimensional CSiO and CGeO: direct-band-gap semiconductors with normal/anomalous auxeticity for solar cells and alkali-metal-ion batteries. (7th September 2022) - Zhu, Yu-Jie; Jiang, Tao; Ye, Xiao-Juan; Liu, Chun-Sheng
Abstract: Two-dimensional (2D) materials provide tremendous opportunities for next-generation energy storage technologies. We theoretically propose 2D group-IV oxides ( α-, β -, and γ -CXO, X = Si/Ge). Among them, α -CXO monolayers, composed of the C-O-X skeleton of silyl (germyl) methyl ether molecules, are the most stable phase. α -CXO possess robust dynamical, mechanical, and thermal stabilities. Remarkably, α -CGeO has an unusual negative Poisson's ratio (NPR). However, α -CSiO displays a bidirectional half-auxeticity, different from all the already known NPR behaviors. The intrinsic moderate direct-band-gap, high carrier mobility, and superior optical absorption of α -CXO make them attractive for optoelectronics applications. A series of α -CXO-based excitonic solar cells can achieve high power conversion efficiencies. Besides, α -CXO monolayers are promising anode materials for sodium- and potassium-ion batteries, exhibiting not only the high specific capacity (532–1433 mA h g −1 ) but also low diffusion barrier and open-circuit voltage. In particular, the specific capacity of K on α -CSiO exhibits one of the highest values ever recorded in 2D materials. The multifunctionality renders α -CXO promising candidates for nanomechanics, nanoelectronics, and nano-optics.